Pengaruh Content Marketing, Affiliate Marrketing, Live Streaming terhadap Impulsive Buying Pada Pengguna Tiktok Shop-Tokopedia (Study Kasus Mahasiswa Universitas Islam Malang). - Sitinjak, Veriananda; Mustapita, Arini Fitria; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to determine and analyze the partial and simultaneous effects of Content Marketing, Affiliate Marketing, and Live Streaming on Impulsive Buying on TiktokShop-Tokopedia users Case study on Malang Islamic University Students, Class of 2021. The type of population to be studied is unlimited, because researchers do not know the exact number of student consumers who make impulsive buying on TiktokShop-Tokopedia. Sampling was carried out by purposive sampling method using the 24 x 5 = 120 respondents. Content marketing, affiliate marketing, and live streaming simultaneously affect impulsive buying. Content Marketing has no effect on Impulsive Buying. Affiliate marketing has an effect on impulsive buying. Live streaming has no effect on impulsive buying.. Keywords: Content Marketing, Affiliate Marketing, Live Streaming, And Impulsive Buying.